2018
DOI: 10.12785/ijpi/060103
|View full text |Cite
|
Sign up to set email alerts
|

Error Analysis of Jordanian First - Year University Students’ English Language Writing at Arab Open University – Case Study

Abstract: The present study aims at analyzing 33 English paragraphs written by first-year students at Arab Open University in Jordan. The participants are from different academic majors, and, all the participants are English foreign language students and face challenges in learning the English language. The tool of the current study was the participants' written paragraphs. All errors committed by the participants were analyzed and classified into different categories. The results showed that the most frequent error cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…Likewise, in spoken English, undergraduate Thai learners produced errors the most of omission type, accounted for more than half of the total errors. In the same way, Al-husban (2018) found that omission and addition were the most two frequent errors commited by Jordanian first-year university students in paragraph writing. Lastly, finding on Saad's and Sawalmeh's study (2014) also revealed that omission accounted for the majority of errors produced by L2 Malaysian learners in role play presentations.…”
Section: Journal Of Scientific Information and Educational Creativitymentioning
confidence: 66%
See 1 more Smart Citation
“…Likewise, in spoken English, undergraduate Thai learners produced errors the most of omission type, accounted for more than half of the total errors. In the same way, Al-husban (2018) found that omission and addition were the most two frequent errors commited by Jordanian first-year university students in paragraph writing. Lastly, finding on Saad's and Sawalmeh's study (2014) also revealed that omission accounted for the majority of errors produced by L2 Malaysian learners in role play presentations.…”
Section: Journal Of Scientific Information and Educational Creativitymentioning
confidence: 66%
“…In this case, grammatical knowledge is inevitably possessed by the writer; otherwise, a writing production can result in communication problem to its readers. In unveiling their research finding pertaining to English essay of comparison and contrast, Karim, et al (2005, in Al-husban, 2018 noted that the students' errors on the usage of verbs lead to miscommunication. That is to say, "Language without grammar would be chaotic and cause the same communication problem, such as grammatical errors in writing and Jurnal Serambi Ilmu: p-ISSN 1693-4849, e-ISSN 2549-2306 Journal of Scientific Information and Educational Creativity speaking" (Batstone, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…A considerable number of studies have been carried out on error analysis in writing (Miko, 2018;Hasan and Munandar, 2018;Al-husban, 2017;Suwastini and Yukti, 2017;Tiarina, 2017;Suhono, 2016;Alfiyani, 2013;Limengka and Kuntjara, much as possible and they should be encouraged to use it. Similarly, Al-husban (2017) conducted a research on university first year students in Jordan to analyse their errors in writing in English and the research demonstrated that categories of errors was omission, addition, misformation and misordering, respectively with respect to their frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Errors happened because the learner is lack of knowledge of the target language and occurred consistently and systematically (Gayo & Widodo, 2018). Errors are caused by lacking knowledge of the language system and cannot be corrected by the learner -self (Al-husban, 2018). In addition, language errors can be caused by interlingual interference and intralingual interference.…”
Section: Review Of Literaturementioning
confidence: 99%